Anatomical site and size of sentinel lymph node metastasis predicted additional axillary tumour burden and breast cancer survival. Issue 6 (21st February 2023) - Lai, Billy Shui‐Wun; Tsang, Julia Y; Li, Joshua J; Poon, Ivan K; Tse, Gary M
Abstract : Aims: Sentinel lymph node (SLN) biopsy is the current standard assessment for tumour burden in axillary lymph node (ALN). However, not all SLN+ patients have ALN metastasis. The prognostic implication of SLN features is not clear. We aimed to evaluate predictive factors for ALN metastasis and the clinical value of SLN features. Methods and results: A total of 228 SLN+ and 228 SLN– (with matched year and grade) cases were included. Clinicopathological features in SLN, ALN and primary tumours, treatment data and survival data were analysed according to ALN status and outcome. Except for larger tumour size and the presence of LVI (both P < 0.001), no significant differences were found in SLN– and SLN+ cases. Only 31.8% of SLN+ cases with ALN dissection had ALN metastasis. The presence of macrometastases (MaM), extranodal extension (ENE), deeper level of tumour invasion in SLN and more SLN+ nodes were associated with ALN metastasis ( P ≤ 0.025). Moreover, isolated tumour cells (ITC) and level of tumour invasion in SLN were independent adverse prognostic features for disease‐free survival and breast cancer‐specific survival, respectively. Interestingly, cases with ITC located in the subcapsular region have better survival than those in cortex (OS: χ 2 = 4.046, P = 0.044). Conclusions: Our study identified features in SLN, i.e. the level of tumour invasion at SLN and tumour size in SLN as useful predictors for both ALN metastasis and breast cancer outcome. The presence of ITC, particularly those with a deeper invasion in SLN, portended a worse prognosis. Proper attention should be taken for their management. Abstract :